The Effect of Particle Size and Time in the Ashing Process on the Yield of Rice Husk Silica Extraction - Rizki Amirullah; Prasdinata Meidaus Kusuma; Ni Ketut Sari (Universitas Islam Raden Rahmat, Malang, 2025)
Indonesia is agrarian country that produces a wide variety of agricultural products. One of the agricultural products that is widely produced is rice. It has the main components of cellulose (38.3%), hemicellulose (31.6%), lignin (11.8%) and silica (18.3%). The percentage of silica (SiO2) in ash ranges from 80% to 99%, but different operating conditions during the ashing process make the silica levels obtained also not the same. In this research, it was carried out with a variety of conditions, namely the burning time and particle size of the rice husk. This research aims to determine the effect of particle size and combustion time on silica obtained from rice husks. To obtain silica from rice husk ash, it is necessary to extract it using 10% KOH solvent for 90 minutes at a temperature of 85°C with a liquid solid ratio of 1:12. The larger the size of the husk, the better the combustion process. The ashing temperature used was 700°C and the highest silica content was 81% at a particle size of 20 mesh and a fumigation time of 120 minutes. And the lowest silica content is 31% at a particle size of 100 mesh and ashing time of 30 minutes.